A213 A NOVEL PH-SENSITIVE OPIOID ANALGESIC THAT IS SELECTIVELY ACTIVATED IN ACIDIC INFLAMMATORY ENVIRONMENTS - Yu, Y (J Can Assoc Gastroenterol, 2020)
BACKGROUND: Opioids drugs are effective analgesics for inflammatory disorders such as inflammatory bowel disease (IBD) but their effects at non-inflammed sites can cause serious morbidity and even death. Exploiting the knowledge that tissue pH in inflamed tissues is acidic (e.g. 6.5–7.0), a novel opioid analgesic, ±)-N-(3-fluoro-1-phenethylpiperidine-4-yl)-N-phenylpropionamide (NFEPP), with a low acid dissociation constant, was developed that selectively activates peripheral µ-opioid receptor (MOPr) at acidic pH. Thus, pH-sensitive binding of NFEPP could selectively inhibit nociceptive nerves in the inflamed colon and have no effect on non-inflamed tissues outside the GI tract. AIMS: Evaluate whether NFEPP causes inhibition of colonic nociceptors at acidic pH’s, which mimic the inflamed colon. METHODS: To evaluate pH sensitive property of NFEPP to activate MOPr, dorsal root ganglia (DRG) neurons from C57BL/6 mice were exposed to the MOPr agonists NFEPP (300nM, 15 min) or DAMGO (100nM, 15 min) or vehicle at pH 6.5 or 6.8 or 7.4. Neuronal excitability was measured by recording the rheobase (minimum current to fire an action potential) using patch clamp recordings of isolated dorsal root ganglia neurons. In parallel ex vivo studies of mouse colon, extracellular recordings were obtained from afferent nerves innervating the distal colon. Afferent responses to probing with von Frey hair (1 gm) were examined before and after exposure to NFEPP (300nM, 5 min superfusion) at pH 6.5 and 7.4 respectively. Oneway ANOVA and post hoc Dunnett and Bonferroni tests were used to analyze the data. RESULTS: In patch clamp studies, NFEPP caused a decrease in DRG excitability at pH 6.5 and 6.8 (increased rheobase 21.3%, p<0.05 and 28.9%, p<0.05 respectively compared to vehicle) but had no effect at physiological pH 7.4. DAMGO, a MOPr agonist, caused inhibition of nociceptor excitability at pH 7.4 (increased rheobase 25.2%, p<0.05 compared to vehicle) as shown in previous experiments, but had no effect at pH 6.5 and 6.8. Vehicle had no effect at the different pH’s. In colonic afferent nerve recordings, NFEPP significantly attenuated afferent response (28.9% P<0.01) to probing at pH 6.5 and this effect was reversed after a 15 min washout. At pH 7.4 NFEPP had no effect on afferent nerve firing. CONCLUSIONS: NFEPP activated MOPr at acidic pH causing inhibition of colonic nociceptors. This pH-selective agonist provides a new strategy to relieve pain at the site of inflammation while being devoid of any of unwanted activity in non-inflamed organs. FUNDING AGENCIES: CCC